Bimetallic Nanoparticles for Antimicrobial Applications - Arora, Naman; Thangavelu, Kavitha; Karanikolos, Georgios N. (Frontiers in Chemistry, 2020)
Highly effective antimicrobial agents are required to control the emergence of new bacterial strains, their increased proliferation capabilities, and antibacterial resistance that acutely influence public health, and several industries including water, food, textiles, and oil & gas. Recently, bimetallic nanoparticles, formed via integration of two different metals, have appeared particularly promising, with antibacterial efficiencies surpassing that of monometallic counterparts due to synergistic effects, broad range of physiochemical properties, and different mechanisms of action. This work aims to provide a review on the latest developed bimetallic and supported bimetallic systems emphasizing in particular on the relation between synthesis routes, properties, and resulting efficiency. Bimetallic nanostructures on graphene, zeolites, clays, fibers, polymers, as well as non-supported bimetallic nanoparticles are reviewed, their synthesis methods and characterization results are illustrated along with their antimicrobial potential against different strains of microbes.